Thermal performance investigation and optimisation of fin type solar air heater - a CFD approach. (2016) - Mathur, Anuj; Agrawal, G.D.
In this paper, single pass fin type solar air heater has been optimised to get better thermal performance using computational fluid dynamics (CFD) technique (Fluent 6.3 and Gambit 2.3). Four important parameters namely mass flow rate, number of fins, fin height and length have been considered. DTRM and RNG k-ε turbulence model were used and the simulation results have been validated with the results of experimental study performed during March, 2012. During the CFD analysis outlet air temperature, air temperature rise, heat gain by the air and instantaneous efficiency has been determined. Simulation results suggest that the SAH should have four fins, i.e., same as in existing SAH but fin length and height should increase from 40 cm to 50 cm and 4 cm to 6 cm respectively for superior performance. In optimised SAH, instantaneous efficiency and useful heat gain improved by 8.35% and 8.24% respectively with air mass flow rate of 0.024 kg/s as compared to SAH.